2019
DOI: 10.1016/j.nicl.2019.102083
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy is associated with shifts in the organization of neural networks in a large incarcerated male sample

Abstract: HighlightsPsychopathy is linked to disruptions in neural information processing.Graph analysis revealed that psychopathy impacts neural network organization.Psychopathy is linked to a hyper-efficiently organized dorsal attention network.Subcortical structures are less central to neural communication in psychopathy.No psychopathy differences were found in default or salience network graph metrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 101 publications
(165 reference statements)
1
10
0
Order By: Relevance
“…Moreover, the amygdala seed revealed psychopathy-linked reduced connectivity between right amygdala and right TPJ. These alterations in functional connectivity are consistent with recent reports of disrupted functional networks association with higher psychopathic traits in incarcerated males ( Espinoza et al, 2018 , Tillem et al, 2019 ). Thus, psychopathy appears to alter connectivity within the social cognition network when inmates viewed morally laden images.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the amygdala seed revealed psychopathy-linked reduced connectivity between right amygdala and right TPJ. These alterations in functional connectivity are consistent with recent reports of disrupted functional networks association with higher psychopathic traits in incarcerated males ( Espinoza et al, 2018 , Tillem et al, 2019 ). Thus, psychopathy appears to alter connectivity within the social cognition network when inmates viewed morally laden images.…”
Section: Discussionsupporting
confidence: 91%
“…Psychopathic traits were not associated with resting-state connectivity within or between the SN and DMN, in contrast to II theory. Previous studies using traditional methods ( Philippi et al, 2015 ) and network modeling ( Lindner et al, 2018 , Tillem et al, 2019 ) have also not consistently found these associations. Thus, emotion and attention impairments observed in psychopathy may not be driven by abnormal communication among regions within the SN or DMN themselves, but instead reflect an imbalance with other networks, such as the CEN.…”
Section: Discussionmentioning
confidence: 64%
“…However, only two studies have been conducted in adults using such an approach. In one study, psychopathic traits were associated with increased centrality of DMN and SN nodes ( Lindner et al, 2018 ), whereas the other study did not find any significant associations with DMN or SN features ( Tillem et al, 2019 ). Notably, these studies were limited by focus on either women from the community or incarcerated offenders.…”
Section: Neural Network and Psychopathymentioning
confidence: 88%
See 2 more Smart Citations